Comparing the Risk Factors of Youth Detained for Running Away or Commercial Sexual Exploitation to more Serious Youth Offenders - Cain, Calli M. (American journal of criminal justice, 2023)
Commercial sexual exploitation (CSE) of minors is a major social justice concern in the U.S. and youth who run away from their home or placement are at an increased risk of experiencing CSE. Runaway youth have higher rates of prior victimization, substance abuse, depression, suicidal behavior, and problems at school compared to youth who do not run away. When youth run away repeatedly, youth may end up arrested and detained for this status offense. Detaining runaway youth and those who are CSE victims can be detrimental to their health and well-being, in addition to being against federal laws. However, it is unknown whether runaway youth and CSE victims, when compared to other juvenile delinquents, present unique risk factors when they enter the juvenile justice system. Using a nationally representative sample of justice-involved youth, this study examines the risk factors of youth who are detained for running away or CSE victimization. This paper then compares these youth whose most serious offense is running away or "prostitution" to the characteristics of youth detained for more serious offenses. Comparing the characteristics of youth incarcerated for running away or CSE victimization to other incarcerated youth has not yet been done with a nationally representative sample. This study finds significant differences in many of the characteristics among runaway and sexually exploited youth who are detained, compared to youth incarcerated for more serious offenses. Policy and programs recommendations are given to reflect of the unique needs of these vulnerable youth.